2022
DOI: 10.3389/fpsyg.2022.990056
|View full text |Cite
|
Sign up to set email alerts
|

The negative footprint illusion in environmental impact estimates: Methodological considerations

Abstract: Past research has consistently shown that carbon footprint estimates of a set of conventional and more environmentally friendly items in combination tend to be lower than estimates of the conventional items alone. This ‘negative footprint illusion’ is a benchmark for the study of how cognitive heuristics and biases underpin environmentally significant behavior. However, for this to be a useful paradigm, the findings must also be reliable and valid, and an understanding of how methodological details such as res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Encouraging such individuals to consume insects might inadvertently diminish their willingness to engage in other environmentally beneficial actions. Similarly, labelling insect-based products as "sustainable" might trigger the "negative footprint illusion" (Gorissen & Weijters, 2016;Holmgren, Andersson & Sörqvist, 2018;Threadgold et al, 2021;Sörqvist & Holmgren, 2022). This illusion may lead consumers to believe that purchasing these "green" products does not add to their environmental footprint, potentially causing an increase in their overall consumption of these products.…”
Section: Potential Rebound Effectsmentioning
confidence: 99%
“…Encouraging such individuals to consume insects might inadvertently diminish their willingness to engage in other environmentally beneficial actions. Similarly, labelling insect-based products as "sustainable" might trigger the "negative footprint illusion" (Gorissen & Weijters, 2016;Holmgren, Andersson & Sörqvist, 2018;Threadgold et al, 2021;Sörqvist & Holmgren, 2022). This illusion may lead consumers to believe that purchasing these "green" products does not add to their environmental footprint, potentially causing an increase in their overall consumption of these products.…”
Section: Potential Rebound Effectsmentioning
confidence: 99%
“…Research has shown that consumers, when faced with a combination of green and non-green products, wrongly estimate the total environmental footprint of this combination to be lower than the footprint of the same non-green product alone, a bias referred to as 'the Negative Footprint Illusion' [8]; for a review, see [9]. For example, when consumers are asked to estimate the environmental impact of a burger (non-green) and an eco-labeled salad (green), they will erroneously combine the footprint of both products into an average instead of adding up the environmental impact of both the burger and the salad.…”
Section: Introductionmentioning
confidence: 99%